Diagnostic Accuracy of Transvaginal Ultrasound and Magnetic Resonance Imaging for Adenomyosis: Systematic Review and Meta‐Analysis and Review of Sonographic Diagnostic Criteria. (27th January 2021) - Liu, Linly; Li, Wentao; Leonardi, Mathew; Condous, George; Da Silva Costa, Fabricio; Mol, Ben W.; Wong, Lufee
Abstract : We aim to first systematically review and perform a meta‐analysis of the diagnostic accuracy of transvaginal ultrasound (TVUS) and magnetic resonance imaging (MRI) and, second, to evaluate the accuracy of various sonographic diagnostic criteria for adenomyosis. A search of PubMed and Embase yielded 32 eligible studies. In diagnosing adenomyosis, the diagnostic performance of TVUS was found to be high and comparable to the performance of MRI. Of the eight sonographic criteria, only five were assessable. The best individual criterion was echogenic subendometrial lines and buds. Limited data exist for the various sonographic criteria, and further studies are required to compare their performance.